2007
DOI: 10.3766/jaaa.18.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Evaluate Audiologic Counseling Skills

Abstract: This study describes the development of an instrument designed to evaluate audiologic counseling skills. In simulated counseling sessions, a trained actor portrayed a parent, and ten graduate audiology students role-played counseling sessions as audiologists informing the "parent" that her infant has a hearing loss. The ten sessions were videotaped, and three raters viewed the taped sessions while evaluating counseling skills with a new evaluation tool, the Audiologic Counseling Evaluation (ACE). The ACE was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Teaching students how to build a history with the client, and to be more aware of clients' responses to history questions in the initial stage of the appointment may help them better tailor rehabilitation recommendations for clients, increase clinical efficiency, and increase long-term adherence to their rehabilitation goals. While little published literature explores current practice in teaching communication and patient-centred practice, academics have flagged that such skills are either taught via the hidden curriculum, or are poorly represented relative to other audiology topics in postgraduate degrees (Atkins, 2007;English et al, 2007). Despite this, the expectation that audiologists possess mastery of counselling skills is observed in Scope Of Practice documents found in many countries (e.g.…”
Section: Clinical Implications For Optimizing Clients' Hearing Rehabimentioning
confidence: 99%
“…Teaching students how to build a history with the client, and to be more aware of clients' responses to history questions in the initial stage of the appointment may help them better tailor rehabilitation recommendations for clients, increase clinical efficiency, and increase long-term adherence to their rehabilitation goals. While little published literature explores current practice in teaching communication and patient-centred practice, academics have flagged that such skills are either taught via the hidden curriculum, or are poorly represented relative to other audiology topics in postgraduate degrees (Atkins, 2007;English et al, 2007). Despite this, the expectation that audiologists possess mastery of counselling skills is observed in Scope Of Practice documents found in many countries (e.g.…”
Section: Clinical Implications For Optimizing Clients' Hearing Rehabimentioning
confidence: 99%
“…Additionally, students believed that adding this type of practice and evaluation would very likely be beneficial to other audiology students. The work of English et al (2007) has shown that SP assessment is advantageous in both teaching and evaluating counseling abilities.…”
Section: Using Sps For Summative Assessmentmentioning
confidence: 99%
“…In summarising much of this literature, Hill To determine if SP training leads to measurable improvements in audiology student clinical skills, a reliable tool for measuring these skills is needed. To the authors' knowledge, only one such tool has been published for use in audiology education -the Audiologic Counseling Evaluation (ACE: English et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, there is currently no suitable published tool to accurately measure the performance of audiology students as they work with SPs in order to determine whether such improvements have been made. to evaluate audiologic counselling skills (English et al, 2007). These questions incorporate 77 desirable counselling behaviours and are organized into seven categories: getting started, breaking the news, assessing parents' understanding of/reaction to the situation, eliciting concerns, giving a time frame for action, suggesting specific actions while waiting for the follow-up appointment, and general considerations.…”
Section: Limitations Of Use Of Sps In Audiologymentioning
confidence: 99%
See 1 more Smart Citation